Effects of Tamarix removal on the community dynamics of riparian birds in a semiarid grassland. Issue 5 (27th January 2017) - Raynor, Edward J.; Cable, Ted T.; Sandercock, Brett K.
Abstract: Invasion of riparian habitats by non‐native plants is a global problem that requires an understanding of community‐level responses by native plants and animals. In the Great Plains, resource managers have initiated efforts to control the eastward incursion of Tamarix as a non‐native bottomland plant ( Tamarix ramosissima ) along the Cimarron River in southwestern Kansas, United States. To understand how native avifauna interact with non‐native plants, we studied the effects of Tamarix removal on riparian bird communities. We compared avian site occupancy of three foraging guilds, abundance of four nesting guilds, and assessed community dynamics with dynamic, multiseason occupancy models across three replicated treatments. Community parameters were estimated for Tamarix ‐dominated sites (untreated), Tamarix ‐removal sites (treated), and reference sites with native cottonwood sites ( Populus deltoides ). Estimates of initial occupancy ( ψ 2006 ) for the ground‐to‐shrub foraging guild tended to be highest at Tamarix ‐dominated sites, while initial occupancy of the upper‐canopy foraging and mid‐canopy foraging guilds were highest in the treated and reference sites, respectively. Estimates of relative abundance for four nesting guilds indicated that the reference habitat supported the highest relative abundance of birds overall, although the untreated habitat had higher abundance of shrub‐nesters than treated or reference habitats. Riparian sites where invasive Tamarix is dominant in the Great Plains can provide nesting habitat for some native bird species, with avian abundance and diversity that are comparable to remnant riparian sites with native vegetation. Moreover, presence of some native vegetation in Tamarix ‐dominated and Tamarix ‐removal sites may increase abundance of riparian birds such as cavity‐nesters. Overall, our study demonstrates that Tamarix may substitute for native flora in providing nesting habitat for riparian birds at the eastern edge of its North American range.